The radical SAM enzyme EpeE exhibits distinct site reactivity during the biosynthesis of the RiPP natural product epipeptide - William G. Walls; Hao Yang; Madeline B. Ho; William E. Broderick; Brian M. Hoffman; Joan B. Broderick (Proceedings of the National Academy of Sciences, 2026)
Radical S -adenosyl- l -methionine (SAM) enzymes figure prominently in the formation of ribosomally synthesized and posttranslationally modified peptides (RiPPs), where they catalyze peptide modifications including epimerization, thioether crosslink formation, and peptide backbone splicing. Here, we use rapid freeze-quench trapping together with electron paramagnetic resonance and electron-nuclear double resonance techniques to probe the mechanistic steps of the two epimerization reactions catalyzed by the radical SAM enzyme EpeE during conversion of its peptide substrate to the epipeptide natural product. Use of the EpeE C223S variant facilitated trapping and characterization of Cα radical intermediates, supporting a central role for C223 in the proposed epimerization mechanism. We showed that both wild-type and C223S EpeE with bound SAM and peptide substrate form the organometallic intermediate Ω upon reaction, and that thermal annealing of Ω results in conversion to an organic radical intermediate. Freeze-quenching at longer times allowed us to directly trap the organic radical intermediate, and isotopic labeling together with use of substrate variants allowed for detailed characterization of the substrate radical intermediates. The results revealed that while LC–MS enzymatic assays point to Ile12 as the initial site of epimerization, freeze-quench EPR reveals that Val4 is the preferred site for initial Cα radical formation. These apparently conflicting results were resolved by the observation that the Ile12 Cα radical is more efficiently quenched to form the d -Ile, thus providing insights into the determinants for substrate binding and epimerization by EpeE.